Pengaruh Motivasi Belajar Siswa Pasca terjadinya Covid-19 - Sofyan Abdi; Annisa Fitria; Tazkia Aulia; Naila Hijriah; Putri Luvita Sari; Siti Nurjanah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine students' learning motivation after the Covid-19 pandemic. Apart from that, we also want to know the impact of online learning on student learning motivation during the Covid-19 pandemic, as well as teachers' efforts to increase student learning motivation after the Covid-19 pandemic. The research method used is descriptive quantitative. The total population was 68 respondents through general questionnaire distribution, using random sampling. This research instrument uses a questionnaire in the form of a questionnaire via Google Form for students in general. The research results are based on data obtained through SPSS 22 in the Case Processing Summary, the number of data or respondents (N) is 100%, meaning that all respondents' answers are filled in, so the number is 100% valid.